Pengaruh Nano Silika Terhadap Nilai Karakteristik Aspal Pen 60/70 - Angga Wibowo; Karica Maulidina Hakim; Siegfried Syafier (LPPM Universitas Sangga Buana, 2025)
Roads are very important because they help the economy of a region grow. Many roads are still poorly designed and constructed, especially in Indonesia. One way to improve the quality of asphalt is to add additives. One material that could make asphalt more valuable and be used as an additive is nanomaterial. This test was done to learn about pen 60/70 asphalt with 2% and 4% nano silica additives. The test uses an experimental research method. It involves testing in the laboratory. The results of testing pen 60/70 asphalt with 2% and 4% nano silica additives showed an increase in values for penetration, softening point, flash point, viscosity, and specific gravity, and a decrease in values for ductility, solubility, and oil weight loss (TFOT).